IL-6 and G-CSF production resulting from lung cancer in an HIV patient. (2020) - Kawakami, Naoki; Namkoong, Ho; Masaki, Katsunori; Kurebayashi, Yutaka; Shimoda, Masayuki; Kotani, Hiroshi; Fujiwara, Hiroshi; Hasegawa, Naoki
Abstract: Increasing reports have noted an increased prevalence of lung cancer in human immunodeficiency virus (HIV)-positive patients with poor prognosis. A 51-year-old HIV-positive man was diagnosed with stage IV squamous cell lung cancer. He had high grade spike intermittent fever and persistent elevation of the white blood cell count as well as C-reactive protein (CRP) levels. Although we suspected opportunistic infections, we did not detect any infection. The autopsy showed positive immunostaining for Interleukin-6 (IL-6) in plasma cells of the stromal regions and G-CSF in tumor cells, which were considered responsible for his significant tumor fever, leukocytosis and high titers of CRP. This case report highlights the need to consider cytokine-producing tumor as a differential diagnosis of fever and high inflammatory status in HIV-positive cancer patients.